Isomerization of Keggin Al13 Ions Followed by Diffusion Rates. Issue 52 (23rd November 2016) - Oliveri, Anna F.; Colla, Christopher A.; Perkins, Cory K.; Akhavantabib, Noushin; Callahan, Joseph R.; Pilgrim, Corey D.; Smart, Scott E.; Cheong, Paul H.‐Y.; Pan, Long; Casey, William H.
Abstract: The solution chemistry of aluminum has long interested scientists due to its relevance to materials chemistry and geochemistry. The dynamic behavior of large aluminum–oxo‐hydroxo clusters, specifically [Al13 O4 (OH)24 (H2 O)12 ] 7+ (Al13 ), is the focus of this paper. 27 Al NMR, 1 H NMR, and 1 H DOSY techniques were used to follow the isomerization of theϵ‐Al13 in the presence of glycine and Ca 2+ at 90 °C. Although the conversion ofϵ‐Al13 to new clusters and/or Baker–Figgis–Keggin isomers has been studied previously, new 1 H NMR and 1 H DOSY analyses provided information about the role of glycine, the ligated intermediates, and the mechanism of isomerization. New 1 H NMR data suggest that glycine plays a critical role in the isomerization. Surprisingly, glycine does not bind toAl30 clusters, which were previously proposed as an intermediate in the isomerization. Additionally, a highly symmetric tetrahedral signal ( δ =72 ppm) appeared during the isomerization process, which evidence suggests corresponds to the long‐soughtα‐Al13 isomer in solution. Abstract : 27 Al NMR, 1 H NMR, and 1 H DOSY techniques were used to follow the isomerization of theϵ‐Al13 in the presence of glycine and Ca 2+ to provide information about ligated intermediates and the mechanism of isomerization. Surprisingly, glycine does not bind toAl30 clusters, and evidence for the long‐soughtα‐Al13 isomer was found (see figure).